Analisis Pengaruh Pertumbuhan Ekonomi, Dana Alokasi Khusus dan Ketimpangan Pendapatan Terhadap IPM di Kabupaten Mimika - Putry, Anastasya Tandi Datu; Tuasela, Anjte (Journal of Economics and Regional Science, 2023)
This study aims to know the impact of economic growth, specific allocations and income inequality on the IPM in Mimika districts both partially and simultaneously. The method that researchersuse is the sociative method. The data-collection tecnique that researchers are using is a documentary tecnique by picking up data that has already been published by the statistical center. The analysis tool used in this study is linear regression. The study shows that in part economic growth, specific allocations and income inequality do not affect the IPM in Mimika district and in the simultaneous economic growth, specific allocation funds and income inequality affect the IPM in Mimika’s district